Mechanical properties of low carbon and sustainable building block uitilising oil palm trunk fiber / Mazlina Mohamad, Zakiah Ahmad and Balqis Md Yunus - Mohamad, Mazlina; Ahmad, Zakiah; Md Yunus, Balqis (Research Management Institute (RMI), 2013)
Cement block has been used in the construction of low-cost housing due to its bigger surface area when compared to brick. Another advantageous of cement blocks is that they require less cement mortar and less labour during construction of housing units. Nowadays cement block weight has been an issue in the construction industry. As the building become higher and enormous, the block weight will become a significant factor in the design and hence as the determinant for the economical factor in the construction cost. Moreover, the use of high cement based building block also reduces the thermal comfort index of the building. In order to overcome this issue, lightweight block will be developed by introducing the use of natural fiber namely oil palm trunk fiber at high percentage in order to reduce the amount of cement and sand. Studies have been conducted on the use of OPTF (Ahmad and Mohd Saman, 2003) for concrete but the percentages used was very little, i.e 5%. The function of the fiber is just to increase the mechanical properties and improve the toughness. This also did not solve the problem of abundance wastage of OPTF at the oil palm plantation. The focus of this project is to show that fibres processed from the trunk of the oil palm tree, can be utilized in the production of bio-cement composite block with satisfactory engineering properties and dimensional stability. In this work; an investigate will be made on the potential of using oil palm trunk fiber in the manufacturing of cement block by adding high percentage of fiber with the addition of foam mortar to enhance the lightness of the block. Studies also include the water absorption characteristics and bondability test between foam cement mortar and fibers. A new shape of block will also be proposed to reduce the use of cement mortar to connect individual unit and longer man-hours during construction.